2064. Incidence and Risk Factors for Microscopic Hematuria in a US Military HIV Cohort. (15th December 2022) - Wachs, Stephanie; Xu, Xiaohe; Daniels, Colton; Sunil, Thankam; Telu, Kalyani; Colombo, Rhonda E; Lalani, Tahaniyat; Berjohn, Catherine M; Ganesan, Anuradha; Agan, Brian; Okulicz, Jason F; Lindholm, David A
Abstract: Background: Microscopic hematuria (MH) is a common finding on screening urinalyses in persons living with HIV (PLWH); however, a study in the pre-HAART era revealed that a complete urologic evaluation was generally non-diagnostic in young males with a benign history and normal renal function. Recent studies have shown a decreased incidence of hematuria in PLWH in the HAART era. We performed a nested case-control study in the prospectively enrolled US Military HIV Natural History Study (NHS) to evaluate characteristics of PLWH with and without MH. Methods: We evaluated male participants diagnosed with HIV and enrolled in the NHS Jan 2007 to Dec 2019. MH cases were defined as having at least one urinalysis with ≥5 RBCs/hpf. We used descriptive statistics to compare cases and controls with respect to demographics, comorbidities, and laboratory findings to determine risk factors for MH. Cox regression models evaluated for independent associations with the development of MH since HIV diagnosis. Results: Of 829 included participants, 142 (17.1%) had MH, of whom 87 (61.3%) had only one MH event. Cases had a shorter mean duration of study follow-up but more analyzable urinalyses per participant. There were no significant differences between cases and controls in demographics, CD4 count nadir, time from HIV diagnosis to HAART initiation, or inclusion of tenofovir disoproxil fumarate (TDF) in initial regimen. On univariate analysis, more cases had a history of urinary tract infection (UTI) or a hypertension diagnosis through the time of incident MH compared to controls, but were less likely to have proteinuria or pyuria at the time of MH. Cox regression models revealed that a history of UTI increased the hazard for MH (HR 2.07, p < 0.05). In contrast, the presence of proteinuria (HR 0.42, p< 0.01) and TDF use (HR 0.56, p< 0.05) decreased the hazard for MH compared to controls. Conclusion: A history of UTI, though not concurrent pyuria, was associated with an increased hazard for MH. The use of TDF in the initial HAART regimen and the presence of proteinuria were protective against hematuria. Future studies are needed to clarify these findings; however, they provide reassurance that in a young, otherwise healthy cohort, MH is typically self-limited and unrelated to intrinsic renal pathology, comorbidity, or HIV-related factor. Disclosures: All Authors : No reported disclosures.